Numerical Study of a Reciprocal Flow Porous Media Burner Using a Turbulence Model - Henriquez-Vargas, L; Donoso-Garcia, P (Begell House Inc., 2022)
This paper presents two–dimensional simulations of turbulent porous media combustion of a methane–air mixture in a reciprocal flow burner. Transport equations were written in their time and volume averaged form, and the statistical turbulence model k-ε was applied to simulate turbulence generation due to the porous matrix. FLUENT was used to simulate the combustor, User–Defined–Function interfaces for extra terms involving turbulence were incorporated into the solver interface, and macros programming allowed to periodically reverse the gas flow direction. The study includes the production of thermal NOx modeled by the extended Zeldovich mechanism. For a set of superficial velocity values of the gas mixture in a single input single output configuration of the reactor, the amount of fuel that allowed to maintain a stable combustion was sought. Then, for the reciprocal flow reactor configuration, the half–cycle time that allowed to confine the combustion front in the reactor central region was determined. Two heat extraction conditions in the lateral areas were studied. It was found that an increase in the thermal load of the reactor is accompanied by peaks of higher temperatures, which are accentuated when the energy losses to the surroundings are diminished. A displacement of the combustion front was observed due to the fluctuation of internal heat recirculation and inertial effects. The rate of formation of NOx depends on the thermal levels that are reached as a product of the combustion reaction. This rate is favored by an increase of the burner thermal load and a low rate of extraction of heat toward the surroundings. © 2022 by Begell House, Inc.